HUBUNGAN SHORT TERM MEMORY SISWA KELAS X DARI SUDUT PANDANG NEUROSAINS DI SEKOLAH MENENGAH ATAS DENGAN HASIL BELAJAR MATEMATIKA - Malau, Evi Ervera; Nimade, Satianingsih; Rudhito, Marcellinus Andy (Jurnal Karya Pendidikan Matematika, 2024)
One of the important abilities in a person's cognitive is the ability of memory, one of which is short-term memory (STM). This study investigates the relationship between Short-Term Memory (STM) and math learning outcomes. The researcher conducts a literature review to gather information and then performs an experiment to measure STM in a class of grade X students in a private school in Bekasi City. The study discusses various information about STM and its connection to students' math learning outcomes. The researcher develops an instrument to measure memory span and administers a test to obtain STM scores, correlating with student learning outcomes using Pearson simple correlation analysis. The results reveal a very low correlation (r=0.104) between STM and grade X learning outcomes in this study. The study concludes that STM does not significantly impact students' learning outcomes since long-term memory is where learners store their general knowledge, school learnings, and personal memories. It suggests that students must review previously studied materials before being assessed to achieve optimal learning results. Other factors that affect learning outcomes include students' psychological factors like interest, intelligence, talent, motivation, and cognitive abilities.